En mode REC[ORD] - Jean-Jacques Castéret (In Situ)
The wave of sound recordings of traditional music and dance that spread throughout France and Europe from the 1960s onwards led to the creation of documentary collections, often decades after the collections were made, and we are now seeking to gain a clearer understanding of their origins and scope. This article looks at the wide variety of recordings and the trajectories of collectors who are largely unknown or even unsuspected. Their autobiographical testimonies describe dynamics that are in part distinct, yet expressed in the same societal in-between, all nourished by frustrations and, against the backdrop of social protest in the late 1960s, aspirations to build a new world. These trajectories between two worlds, opposing town and country, capital and periphery, also take place in an in-between period that is bound to raise questions, the time of an invisible initiation (Fabre) with tape recorder in hand, of which the resulting archive and autobiographical narrative are the audible mark.